Caracterização magnética de compósitos multiferróicos particulados Pb(Zr0,52Ti0,48)O4/CoFe2O4 - Jimenez, Korllvary Rhanddy Charles Parra (2014)
This work was studied the magnetic and electrical properties of particulate multiferroic composite Pb (Zr0,52Ti0,48) O4 / CoFe2O4 (PZT / CFO) (0-3 type) prepared by the polymeric method of Pechini and sintered by ultra-rapid method in microwave and conventional oven, with two molar concentration (80/20 and 50/50). These samples were characterized by ferroelectricity measurements as a function of applied electric field. And magnetization, magnetostriction and magnetoelectric effect as a function of magnetic applied. The main goal of our study was to analyze and characterization of the magnetic and magnetoeletric dependence of particulate composites PZT / CFO, where these samples exhibits two different grains size distribution of cobalt ferrite when compared of grain size average of PZT matrix, with two methods of sintering. We observed these samples present a dependence of the magnetic properties with the methods of sintering and the average grain size of ferrimagnetic phase. This effect was observed in the electric polarization of the ferroelectric PZT. In addition, differences were observed in the magnetic properties 5K and 300K, especially in the coercive field, for samples of cobalt ferrite and composite PZT / CFO 50/50, associated to differences of apparent densities.